2009
DOI: 10.1007/s00534-009-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Can hyperbaric oxygenation decrease doxorubicin hepatotoxicity and improve regeneration in the injured liver?

Abstract: Based on our results, we conclude that HBO treatment has the potential to diminish doxorubicin-related hepatotoxicity and improve regeneration in the injured liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In the case of acute liver damages, the ALT escalates more significantly than the AST [18]. This result shows that the injection of doxorubicin damages liver cells, corresponding to the results of other studies [6,19].…”
Section: Discussionsupporting
confidence: 82%
“…In the case of acute liver damages, the ALT escalates more significantly than the AST [18]. This result shows that the injection of doxorubicin damages liver cells, corresponding to the results of other studies [6,19].…”
Section: Discussionsupporting
confidence: 82%
“…However, the use of HBO in combination with DOX is controversial stemming from seminal work by Upton et al where 7 of 8 rats that were treated twice daily with HBO at 2 ATA died by the fourth week after DOX injection [ 24 ]. While the mortality rate in these rats was attributed to excessive free radical formation, this drastic effect on animal survival has not been replicated in subsequent studies [ 25 , 27 ]. Preliminary observations regarding the effects of HBO therapy concurrent with DOX treatment on cardiac function were published in 2008 when Karagoz et al reported partial improvements in ejection fraction and fractional shortening in rats that had received 15 doses of DOX (1 mg/kg/dose) and a 90-min session of HBO at 2.4 ATA 5 days per week over a 4-week period [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when used as a preventative method, HBO has been shown to improve ischemic tolerance of the brain, spinal cord, liver, heart, and skeletal muscle through increases in antioxidant enzymes and anti-inflammatory proteins [ 6 , 18 , 19 , 20 , 21 ]. However, evidence on the effects of HBO given in combination with DOX treatment is mixed and poorly understood [ 22 , 23 , 24 , 25 , 26 , 27 ]. This study adds to the limited understanding regarding the safety and efficacy of HBO as a therapy to combat DOX myotoxicity.…”
Section: Introductionmentioning
confidence: 99%